2009
DOI: 10.1080/09638280802356419
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality of life and participation within an outpatient rehabilitation setting

Abstract: Our study demonstrated a strong relationship between quality of life and participation, with change shown using both scales over a period of outpatient rehabilitation. Given the findings, it seems appropriate to use only one of these measures. The WHOQOL-BREF has a wider scope, being useful both to evaluate service delivery in a diverse outpatient population or when measuring an individual over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(19 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…The ability of the WHOQOL-BREF to evaluate change over time was investigated in a study within an outpatient rehabilitation setting. That study concluded that the questionnaire was a useful instrument for outcome measurement [ 17 ]. Also, statistically significant differences were found in all but the social domain, using raw data, between admission and discharge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of the WHOQOL-BREF to evaluate change over time was investigated in a study within an outpatient rehabilitation setting. That study concluded that the questionnaire was a useful instrument for outcome measurement [ 17 ]. Also, statistically significant differences were found in all but the social domain, using raw data, between admission and discharge.…”
Section: Discussionmentioning
confidence: 99%
“…This model is the foundation of the multidisciplinary treatment approach in rehabilitation. Today the International Classification of Functioning (ICF) is adopted as a framework for rehabilitation, and an important goal in rehabilitation is to increase QOL of patients [ 16 , 17 ]. Currently no normal values for QOL of Dutch rehabilitation outpatients are available, which are essential for a correct comparison between rehabilitation outpatients, the general Dutch population and psychiatric outpatients.…”
Section: Introductionmentioning
confidence: 99%
“…11 Mobility is considered an important rehabilitation goal, [12][13][14][15] but additional factors also affect the functioning and well-being of amputees. Quality of life (QoL) is increasingly being recognized as an important outcome of rehabilitation programmes, 16,17 and also as an indicator to assess adjustment to prosthesis. 18 QoL has mainly been used to compare the efficacy of interventions, such as limb salvage procedure versus amputation, [19][20][21][22] or to compare amputees and other diseased populations.…”
Section: Introductionmentioning
confidence: 99%
“…Assessing the individual's participation rate in terms of education, social activities, and leisure time is required for the development of interventions, which enable a long life with a good QoL ( 32 ). In future studies on BOI and QoL, standardized instruments to measure participation such as questionnaires for patients and carers could be used ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%